Virtual Screening Based on Ensemble Docking Targeting Wild‐Type p53 for Anticancer Drug Discovery. Issue 7 (26th June 2019) - Li, Xin; Zhang, Xin‐Xin; Lin, Yu‐Xi; Xu, Xi‐Ming; Li, Li; Yang, Jin‐Bo
Abstract: The tumor‐suppressor function of p53 makes it an attractive drug target. Efforts were mostly put on stabilization of the functional p53 or reactivation of mutated p53. Previous studies have shown that small molecules targeting Loop1/Sheet3 (L1/S3) can reactivate the R175H‐p53 and stabilize p53 in vitro . Since the L1/S3 pocket is shared by the mutate and the wild type (WT) p53, virtual screening is introduced to identify natural products targeting the L1/S3 of WT p53. Considering the high flexibility of Loop1, ensemble docking method is utilized for different clusters of the L1/S3. Seven conformations were chosen for docking. As one of the 181 selected candidates, torilin not only improved p53 activity, but also increased p21 protein expression level, which lies downstream of p53, therefore suppressing HCT116 cancer cell growth. Torilin may covalently bind to Cys124 of p53 by 2‐methyl‐2‐butenal (2M2B) group, as torilin derivatives, which do not contain the 2M2B group, were not able to increase the p53 transcription activity. In conclusion, this study demonstrated that L1/S3 of WT‐p53 is a druggable pocket, and torilin has a potential cytotoxicity through activating the p53 pathway. Abstract :